Antimonopoly compliance in the Republic of Armenia - Hovhannisyan, Arsen; Khachikyan, Martin (Bulletin of Yerevan University C: Jurisprudence, 2023)
The article discusses the legal regulations related to antimonopoly compliance programs in the Republic of Armenia and the necessary actions to ensure their effective implementation. The circumstances and factors that business entities should take into account when drafting antimonopoly programs were also discussed. Through the implementation of warning and prevention procedures, it is possible to practically improve the compliance of business entities with the antimonopoly legislation, because the application of milder measures of administrative responsibility by the authorized body provides a unique opportunity to correct and prevent possible violations. Acceptance of the antimonopoly compliance program does not imply its implementation, because a number of business entities can stipulate the acceptance of the act as a tool for reducing the fine imposed in the event of a possible violation of the antimonopoly legislation in the future, as a result of which it is necessary that the Commission for the Protection of Competition is not limited only to the presence of a compliance program at the business entity, but also through other appropriate mechanisms, find out whether the relevant business entity is guided and was previously guided by the compliance act adopted by it, or whether its existence is formal. The article also singles out the conditions, the simultaneous presence of which will make it possible to ensure the effective implementation of the antimonopoly compliance program.